PENGARUH TERPAAN ONLINE CUSTOMER REVIEW DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN SERUM WHITELAB - Ajeng Rengganis, Sekar; Pradekso, Tandiyo; Luqman, Yanuar (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
The Whitelab Serum, as one of the beauty products, has experienced a decline in popularity. In 2022, Whitelab ranked fifth in the sales of best-selling serums on ecommerce platforms during the July-August period, with a total sale of 104,600. However, in 2024, Whitelab has dropped to the eleventh position in the sales of best-selling serums on Shopee. This study is an explanatory quantitative research type. The Total Utility theory is used to explain the relevance of price perception to purchasing decisions. The simple linear regression test on online customer reviews' impact on purchasing decisions shows a significance value of 0.584 (>0.05), thus rejecting the hypothesis, indicating that online customer reviews do not have an influence on the purchasing decision of Whitelab Serum. The significance value of price perception on purchasing decisions is 0.011 (<0.05), therefore accepting the hypothesis that price perception does influence the purchasing decision of Whitelab Serum.